(untitled) (Archives of Mechanics - Test, 2001)
By using the asymptotic method combined with variational approach a new dynamic model of elastic orthotropic plates is derived. This model accounts for rotational inertia and takes into account second order terms U2 and σ2 in the asymptotic expansions of displacements and stresses. To avoid the boundary layer analysis, the boundary conditions for U2 are satisfied in a suitable averaged sense. Convergence theorem is formulated. Influence of the second-order terms on plate response in the static case is investigated.